IMPACT OF FOLIAR APPLICATION OF POLYAMINE AND IRON SULPHAT ON GROWTH AND FLOWERING OF SNAPDRAGON (Antirrhinum majus L) - M. N. Muslim,; A. N. Badri,; H. A. Hadi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This experiment was conducted during 2022-2023 season in private nursery. The aim of the study was to assess the effects of foliar spraying with polyamine and iron sulphate on growth and flowering of the snapdragon plant, Antirrhinum majus L. The experiment focused on two factors. The first factor involved foliar spraying with polyamine at concentrations of 0, 5, 10, and 15 mg.L-1, The plants were treated with polyamine through two rounds of spraying, 15 and 25 days after planting. The second factor involved foliar spraying with iron sulphate at concentrations of 0, 0.1, 0.2, and 0.4 g.L-1 through two rounds 15 and 25 days after planting. The study followed a factor experiment design (4×4) based on the Randomised Complete Block Design (RCBD). The research commenced by sowing seeds in cork dishes filled with Peat moss. After two weeks of planting, the plants were fertilized with a chemical fertilizer at a concentration of 2 g.L-1. The findings indicated that applying polyamine through foliar spraying at a concentration of 15 mg.L-1, along with iron sulphate at a concentration of 0.4 g.L-1, had a notable impact on the vegetative and flowering growth traits. These included plant height, chlorophyll content in leaves, and carbohydrates percentage in leaves